"Type D" killer whale genomes reveal long-term small population size and low genetic diversity. (27th March 2023) - Foote, Andrew D; Alexander, Alana; Ballance, Lisa T; Constantine, Rochelle; Galletti Vernazzani Muñoz, Bárbara; Guinet, Christophe; Robertson, Kelly M; Sinding, Mikkel-Holger S; Sironi, Mariano; Tixier, Paul; Totterdell, John; Towers, Jared R; et al.
Abstract: Genome sequences can reveal the extent of inbreeding in small populations. Here, we present the first genomic characterization of type D killer whales, a distinctive eco/morphotype with a circumpolar, subantarctic distribution. Effective population size is the lowest estimated from any killer whale genome and indicates a severe population bottleneck. Consequently, type D genomes show among the highest level of inbreeding reported for any mammalian species ( F ROH ≥ 0.65). Detected recombination cross-over events of different haplotypes are up to an order of magnitude rarer than in other killer whale genomes studied to date. Comparison of genomic data from a museum specimen of a type D killer whale that stranded in New Zealand in 1955, with 3 modern genomes from the Cape Horn area, reveals high covariance and identity-by-state of alleles, suggesting these genomic characteristics and demographic history are shared among geographically dispersed social groups within this morphotype. Limitations to the insights gained in this study stem from the nonindependence of the 3 closely related modern genomes, the recent coalescence time of most variation within the genomes, and the nonequilibrium population history which violates the assumptions of many model-based methods. Long-range linkage disequilibrium and extensive runs of homozygosity found in type D genomes provide the potential basis for both the distinctive morphology, and the coupling of genetic barriers to gene flow with other killer whale populations. Graphical Abstract: